2021
DOI: 10.1002/ece3.7744
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven elevational variation in range sizes of vascular plants in the central Himalayas: A supporting case for Rapoport's rule

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Specifically, the positive effect of climate variability was stronger for species in warmer regions (e.g., lower elevations) than for species in colder regions (e.g., higher elevations). This finding is consistent with previous studies that found that both mean climatic conditions and climate variability are important drivers of species’ range sizes in different taxa (e.g., (Luo et al ., 2011; Chan et al ., 2016; Liang et al ., 2021). Although studies in terrestrial vertebrates have considered the interaction between average environmental conditions and climate variability (Chan et al ., 2016), to our knowledge our study is the first one on woody plants to include these effects when testing the ECVH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, the positive effect of climate variability was stronger for species in warmer regions (e.g., lower elevations) than for species in colder regions (e.g., higher elevations). This finding is consistent with previous studies that found that both mean climatic conditions and climate variability are important drivers of species’ range sizes in different taxa (e.g., (Luo et al ., 2011; Chan et al ., 2016; Liang et al ., 2021). Although studies in terrestrial vertebrates have considered the interaction between average environmental conditions and climate variability (Chan et al ., 2016), to our knowledge our study is the first one on woody plants to include these effects when testing the ECVH.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies in terrestrial vertebrates have considered the interaction between average environmental conditions and climate variability (Chan et al ., 2016), to our knowledge our study is the first one on woody plants to include these effects when testing the ECVH. For example, Liang et al (2021) considered mean environmental variables besides thermal variability in their study of plant elevational ranges. They found that both mean annual temperature and mean annual precipitation had a significant relationship with plant elevational ranges; they did not, however, consider interactions among these and climate variability in their analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations